Dietary protein, exercise, ageing and physical inactivity: interactive influences on skeletal muscle proteostasis. Issue 2 (7th May 2021) - Deane, Colleen S.; Ely, Isabel A.; Wilkinson, Daniel J.; Smith, Kenneth; Phillips, Bethan E.; Atherton, Philip J.
Abstract : Dietary protein is a pre-requisite for the maintenance of skeletal muscle mass; stimulating increases in muscle protein synthesis (MPS), via essential amino acids (EAA), and attenuating muscle protein breakdown, via insulin. Muscles are receptive to the anabolic effects of dietary protein, and in particular the EAA leucine, for only a short period (i.e. about 2–3 h) in the rested state. Thereafter, MPS exhibits tachyphylaxis despite continued EAA availability and sustained mechanistic target of rapamycin complex 1 signalling. Other notable characteristics of this 'muscle full' phenomenon include: (i) it cannot be overcome by proximal intake of additional nutrient signals/substrates regulating MPS; meaning a refractory period exists before a next stimulation is possible, (ii) it is refractory to pharmacological/nutraceutical enhancement of muscle blood flow and thus is not induced by muscle hypo-perfusion, (iii) it manifests independently of whether protein intake occurs in a bolus or intermittent feeding pattern, and (iv) it does not appear to be dependent on protein dose per se . Instead, the main factor associated with altering muscle full is physical activity. For instance, when coupled to protein intake, resistance exercise delays the muscle full set-point to permit additional use of available EAA for MPS to promote muscle remodelling/growth. In contrast, ageing is associated with blunted MPS responses to protein/exercise (anabolic resistance), while physical inactivity (e.g. immobilisation) induces a premature muscle full, promoting muscle atrophy. It is crucial that in catabolic scenarios, anabolic strategies are sought to mitigate muscle decline. This review highlights regulatory protein turnover interactions by dietary protein, exercise, ageing and physical inactivity.